A Bispyrazole Based Porous 2D Luminescent MOF for the Turn‐Off Detection of Pd(II) Ions. Issue 33 (30th August 2019) - Kumar, Sushil; Kaushal, Jolly; Singh, Siddhant; Sharma, Vikas; Kumar, Arun; Tomar, Kapil
Abstract: A novel bispyrazole based porous MOF ({[Zn(MBPz)(Ene)0.5 ]⋅2DMF⋅2H2 O} n (1 )) with open alkene (‐HC=CH‐) and nitrogen sites has been synthesized, as an efficient fluorescent sensor for Pd(II) ions. The MOF exhibits 3D supramolecular structure with open channels having 27.2% porosity. The unsaturated ‐CH=CH‐ moieties are present along the walls of open channels which is favorable for interaction with guest moieties. The cation sensitivity of 1 was evaluated using a series of transition metal ions in DMF. The fluorescence quenching of 1 was demonstrated by an approximately 94% reduction in the emission intensity upon binding to Pd 2+ ions. The emission intensity of 1 at 414 nm has shown a linear response to Pd(II) ion concentration with a detection limit of 4.7 x 10 −7  M. The sensing property of 1 towards Pd(II) ions is attributed to the π electron donation from the alkene bonds present in the ligand (Ene). Abstract : A novel Zn(II)‐MOF (1 ) is synthesized as an efficient fluorescent sensor for Pd(II) ions. The unsaturated ‐HC=CH‐ moieties, favorable for interaction with Pd ions, are present along the walls of open channels.